ANALYZING THE EVALUATION SYSTEM AND METHODOLOGY OF THE RULE OF LAW INDEX (Conferencea, 2024)
The Rule of Law Index, developed by the World Justice Project, serves as a critical tool in assessing the adherence to the rule of law across various countries globally. This thesis undertakes a comprehensive analysis of the evaluation system and methodology employed by the Rule of Law Index to scrutinize its effectiveness and reliability. Through a methodical examination of the index's data sources, criteria, and computational techniques, this study identifies the strengths and potential biases inherent in its current framework. Employing both qualitative and quantitative analysis methods, this research aims to reveal how these factors influence the overall rankings and perceptions of the rule of law worldwide. The findings are intended to provide substantive insights into the index's operational mechanisms and propose targeted recommendations for refining its assessment procedures. This analysis not only contributes to the academic discourse on legal indices but also aids policymakers and legal reformers in understanding and leveraging the Rule of Law Index more effectively.